Coronary artery diameter measurement and Z-score regression equation calculation: a comparative study between Indian children between one to five years residing in and around Kolkata with children of South-East Asia and Western population - Das, Satyaki; Ray, Swapan Kumar; Bhattacharya, Sukanta; Chatterjee, Kripasindhu; Mandal, Pradyut Kumar; Sen, Sukanta (International Journal of Contemporary Pediatrics, 2017)
Background: Congenital coronary anomalies may be isolated, or they may accompany other congenital heart defects, such as Fallot’s tetralogy, transposition of the great arteries or pulmonary atresia. The most common cause of acquired abnormalities of the coronary vessels in children is kawasaki disease (KD). The aim of this study was to find the best model to obtain valid and normally distributed Z-scores for coronary artery (CA) diameters in a large, heterogeneous population of healthy children. Methods: Echocardiography was performed on 300 healthy children. Linear regression models were tested with height, weight, body surface area, and aortic valve diameter. The computed Z scores were tested for normal distribution and stability. Results: CA diameter was best predicted using regression with the body surface area and age in month. The weighted least squares method yielded normally distributed and very stable Z-score estimates for 3 principal CAs. Conclusions: This study showed valid methods to estimate Z scores for CA size in children of all ages. Such Z scores are important for risk stratification in patients with Kawasaki disease.